(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2020)
This study was carried out to determine the presence and quantity of some selected pesticides from soil sediments collected from some ponds and canals located in the Lakshmipur district of Bangladesh. The high performance liquid chromatography (HPLC) technique was used to determine the concentration of pesticide residues. Some soil samples were found to be contaminated with carbamate (carbofuran and carbaryl) and organophosphorus (diazinon) pesticides. The concentration of carbofuran pesticide ranged from 0.303 μg/kg to 1.851 μg/kg. The highest concentration of carbofuran pesticide was found in SSP6 (1.851 μg/kg) and the lowest concentration was found in SSP9 (0.303 μg/kg). Carbaryl pesticide was found to be present in the sediment of only one pond, the concentration being 1.047 μg/kg. Organophosphorus (diazinon) pesticide was found in soil samples and the concentrations ranged from 0.147 μg/kg to 0.759 μg/kg, which were higher than the EEC-recommended limit of 0.1 μg/kg. J. Asiat. Soc. Bangladesh, Sci. 46(2): 191-200, December 2020